2020
DOI: 10.1021/acsomega.0c00991
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of CdS Nanorods on Si Pyramid Surface for Photosensitive Application

Abstract: It is the first time that cadmium sulfide (CdS) nanorods have been fabricated on silicon (Si) pyramid surface by the hydrothermal reaction method. In our work, the Si pyramid morphology is able to increase the adhesion between the CdS seed layer and Si wafer. Hence, it is critical for CdS nanorods to grow successfully. During the fabrication process, the glutathione is used as the complexing agent for the formation of the CdS nanorods. By continuously adjusting the experimental conditions, the thickness of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…[4][5][6][7][8][9] CdSÀ Si NW heterostructures are the most reported ones which can find potential use as nano LED, photodetectors and for photocatalytic hydrogen evolution. [10][11][12][13][14] Recently, our group demonstrated electricity generation from atmospheric moisture utilizing CdSÀ Si NW heterojunction thin films resulting in an output voltage of ~300 mV and an output current of ~300 μA. [15] Lead sulfide (PbS), a narrow band gap material (~0.4 eV) has emerged as an efficient absorbent layer for photovoltaic cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9] CdSÀ Si NW heterostructures are the most reported ones which can find potential use as nano LED, photodetectors and for photocatalytic hydrogen evolution. [10][11][12][13][14] Recently, our group demonstrated electricity generation from atmospheric moisture utilizing CdSÀ Si NW heterojunction thin films resulting in an output voltage of ~300 mV and an output current of ~300 μA. [15] Lead sulfide (PbS), a narrow band gap material (~0.4 eV) has emerged as an efficient absorbent layer for photovoltaic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Different II–VI metal chalcogenides are reported in the literature to form heterojunction structures with Si NW which can be further exploited for advanced applications in various fields including energy generation and photodetectors [4–9] . CdS−Si NW heterostructures are the most reported ones which can find potential use as nano LED, photodetectors and for photocatalytic hydrogen evolution [10–14] . Recently, our group demonstrated electricity generation from atmospheric moisture utilizing CdS−Si NW heterojunction thin films resulting in an output voltage of ~300 mV and an output current of ~300 μA [15] …”
Section: Introductionmentioning
confidence: 99%
“…Hayden et al were the first to report the fabrication of heterostructured nanowires with p‐type Si core and n‐type CdS shell using pulsed‐laser deposition (PLD) for the application as nano LEDs in 2005 [8,9] . Subsequently, there has been quite a few reports involving the application of CdS/Si heterojunction as photodetector [10–18] . A recent work by Lin et al reported the synthesis of CdS quantum dot (QD) decorated vertically aligned Si NWs arrays with enhanced activity and recyclable operability for photocatalytic hydrogen evolution [19] .…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] Subsequently, there has been quite a few reports involving the application of CdS/Si heterojunction as photodetector. [10][11][12][13][14][15][16][17][18] A recent work by Lin et al reported the synthesis of CdS quantum dot (QD) decorated vertically aligned Si NWs arrays with enhanced activity and recyclable operability for photocatalytic hydrogen evolution. [19] The formation of p-n heterojunction at the interface of the Si NWs and the CdS QDs results in an internal electric field which facilitate the separation and transport of the photoinduced charge carriers thereby improving both the photoactivity and photostability of the Si NWs/CdS array composite.…”
Section: Introductionmentioning
confidence: 99%